STRENGTHENING THE DIGITAL SKILLS OF GENERATION Z SANTRI THROUGH TRAINING ON THE USE OF SOCIAL MEDIA AS A MEANS OF BUILDING PERSONAL BRANDING - Ahmad Zulfikar Ali; Moh. Maqbul Mawardi (As-Sidanah, 2026)
The low level of digital literacy among Generation Z Islamic boarding school students is a major obstacle to utilizing technology for effective da'wah. This program aims to provide an understanding of digital literacy and equip students with practical skills in processing creative content to build personal branding. The novelty of this program lies in its intervention targeting traditional Islamic boarding schools with limited infrastructure, an area that is often overlooked in mainstream digital literacy studies. The activities were carried out using a Service Learning (SL) approach, combined with Kurt Lewin's stages of change, to systematically transform students' behavior on social media. The implementation method consisted of four main stages: problem investigation, strategy preparation, action (including vision clarification, behavior change through technical training, and refreezing through assignments), and self-reflection. The results of the activity showed a significant increase in students' understanding of the urgency of personal branding and mastery of digital skills, such as copywriting, graphic design, and video editing, with practical implications for students' ability to produce consistent, independent creative da'wah content. Theoretically, this program demonstrated that the Service Learning method is effective when used in a pesantren environment to accelerate technological adaptation and foster a positive digital identity among Generation Z students.